Labor Migration in the European Union: The case of Central and Eastern Europe - Ondrej Schneider (Charles University in Prague, Institute of Economic Studies (IES), 2021)
This paper examines migration trends in the European Union since the enlargements of 2004-2007, which brought 100 million citizens of eleven Central and Eastern European countries into the EU. We examine country- and regional-level data on migration trends and show how European integration depleted the labor force in new member countries. Several of them lost 10% of their population since 2006, most of it via negative net migration. In 2019, 18% of Romanians, 14% of Lithuanians, 13% Croats, and Bulgarians lived in another EU country. The quantitative analysis shows that migration contributed positively to regional convergence, as every percentage point of net migration increased GDP per capita by roughly 0.01% and reduced unemployment by 0.1-0.2 percentage points. Further analysis will be needed to disentangle aggregate migration effects to quantify its impact on regions that lose their population via migration.
Keywords: F22; F66; J61; O15; R11; R23; 330; migration; labor markets; convergence; European Union